In silico identification of novel antimicrobial peptides from the venom gland transcriptome of the spider Argiope bruennichi (Scopoli, 1772) - Shin, Min Kyoung; Hwang, In-Wook; Jang, Bo-Young; Bu, Kyung-Bin; Yoo, Jung Sun; Sung, Jung-Suk (Frontiers in Microbiology, 2023)
As the emergence and prevalence of antibiotic-resistant strains have resulted in a global crisis, there is an urgent need for new antimicrobial agents. Antimicrobial peptides (AMPs) exhibit inhibitory activity against a wide spectrum of pathogens and can be utilized as an alternative to conventional antibiotics. In this study, two novel AMPs were identified from the venom transcriptome of the spider Argiope bruennichi (Scopoli, 1772) using in silico methods, and their antimicrobial activity was experimentally validated. Aranetoxin-Ab2a (AATX-Ab2a) and Aranetoxin-Ab3a (AATX-Ab3a) were identified by homology analysis and were predicted to have high levels of antimicrobial activity based on in silico analysis. Both peptides were found to have antibacterial effect against Grampositive and -negative strains, and, in particular, showed significant inhibitory activity against multidrug-resistant Pseudomonas aeruginosa isolates. In addition, AATX-Ab2a and AATX-Ab3a inhibited animal and vegetable fungal strains, while showing low toxicity to normal human cells. The antimicrobial activity of the peptides was attributed to the increased permeability of microbial membranes. The study described the discovery of novel antibiotic candidates, AATX-Ab2a and AATX-Ab3a, using the spider venom gland transcriptome, and validated an in silico-based method for identifying functional substances from biological resources.